Spin doctors: An experiment on vague disclosure - Marvin Deversi; Alessandro Ispano; Peter Schwardmann (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2022)
Unfavorable news are often delivered under the disguise of vagueness. Our theory-driven laboratory experiment investigates this strategic use of vagueness in voluntary disclosure and asks whether there is scope for policy to improve information transmission. We find that vagueness is profitably deployed by senders to fool those receivers that lack strategic sophistication. Imposing precise disclosure leads to more easily interpretable messages, but results in fewer sender types disclosing at all. Since non- disclosure also systematically misleads naive receivers, the welfare implications of imposing precision are not obvious. However, our model and experiment show that information transmission and the welfare of naive receivers are improved by policies that impose precision. Our results speak to the rules governing firms' disclosure of quality-relevant information, the disclosure of research findings, and testimonies in a court of law.
Keywords: D82; D83; C72; C92; L15; D04; 330; communication; naivete; flexibility; regulation